Renal and ureteral trauma - Onur, Mehmet Ruhi; Dogra, Vikram S. (Springer-Verlag London Ltd, 2013)
Renal trauma can occur secondary to abdominal trauma or interventional procedures. Renal injury is encountered in 10 % of the abdominal trauma patients. Ureteral injury usually results from iatrogenic causes but can occur from trauma as well. Undetected renal trauma presents with urinoma, perinephric abscess, sepsis, delayed bleeding secondary to arteriovenous fistula or pseudoaneurysm, hypertension, hydronephrosis, calculus formation, and chronic pyelonephritis. Computed tomography is the most sensitive imaging method in detection of renal trauma. Intravenous pyelography, retrograde pyelography, antegrade pyelography, and CT urography can detect ureteral injury. In this chapter, imaging findings of kidney and ureteral trauma are classifications of renal trauma are presented. © Springer-Verlag London 2013.